2003
DOI: 10.1111/j.1572-0241.2003.07257.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and clinical impact of antinuclear antibodies in primary biliary cirrhosis

Abstract: Antinuclear antibodies reactivities are present in more than half of primary biliary cirrhosis patients and target diverse autoantigens located in distinct subnuclear structures. Anti-gp210 identifies a subgroup of primary biliary cirrhosis patients with more serious liver disease. Positivity for anti-Sp100, anti-gp210, and anti-lamin B receptor, either alone or in combination, may act as a serologic marker of antimitochondrial antibodies negative primary biliary cirrhosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
76
5
5

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 192 publications
(93 citation statements)
references
References 38 publications
7
76
5
5
Order By: Relevance
“…[22][23][24][25] However, this finding needs to be validated in larger longitudinal studies. Sp100 and gp210 proteins are the main antigenic targets of anti-ND and anti-nuclear pore complex antibodies, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…[22][23][24][25] However, this finding needs to be validated in larger longitudinal studies. Sp100 and gp210 proteins are the main antigenic targets of anti-ND and anti-nuclear pore complex antibodies, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The suggestion ensues that the clinicians using a panel of PBC-specific ANAs may have at their disposal a "positive" tool in the diagnosis of AMA-negative PBC. The findings of Muratori et al should be validated in larger series as the authors themselves appropriately advocate (12). The possibility that PBC-specific ANAs may become an essential marker for AMA-negative PBC is indirectly suggested by earlier immunofluorescence studies where the majority (6) or the totality (4) of such patients was found to be ANA positive.…”
Section: Positive Markers In Ama-negative Pbcmentioning
confidence: 99%
“…Two PBC-specific ANA immunofluorescence patterns have been identified [11,12] : "multiple nuclear dots", corresponding to the antigens Sp100 and Sp140, promyelocytic leukemia (PML) nuclear body proteins and small ubiquitin-like modifiers (SUMOs) [13,14] , and "nuclear membrane" (rim), caused by anti-nuclear envelope antibodies (ANEAs), such as gp210 and nucleoporin p62 [15,16] . The anti-gp210 antibodies are highly specific for PBC and are associated with disease activity and severity [17,18] . Nakamura et al [19] found that the expression of gp210 is markedly increased on the nuclear envelope of small bile ducts and sometimes at infiltrating mononuclear cells in the portal area and/or periportal hepatocytes in PBC and this expression was positively correlated to disease activity.…”
Section: Introductionmentioning
confidence: 99%